1996
DOI: 10.1161/01.res.79.2.153
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C Isoform Expression in Normal and Failing Rabbit Hearts

Abstract: Protein kinase C (PKC) is activated by alpha-adrenergic stimulation. Molecular analysis showed that PKC consists of a family of at least 12 isozymes. Studies of their distribution in the heart showed conflicting results. The first goal of our study was thus to characterize cardiac PKC in normal rabbits. PKC plays an important role in gene expression, cell growth, and differentiation and is involved in the hypertrophy phase of cardiac overload, but since its expression has never been evaluated in heart failure,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 36 publications
1
47
0
Order By: Relevance
“…PKCε increased significantly in spontaneously hypertensive rats (SHR), which exhibit genetic hypertension similar to that of Dahl salt-sensitive rats (37). In congestive heart failure, PKCα, β, γ, and ε decreased and PKCζ was not significantly modified when rabbits underwent heart failure induced by a double hemodynamic overload (aortic insufficiency followed by an aortic stenosis) (38). PKCα and β increased and PKCε was not significantly changed in the failing human heart due to dilated and ischemic cardiomyopathy (15).…”
Section: Discussionmentioning
confidence: 99%
“…PKCε increased significantly in spontaneously hypertensive rats (SHR), which exhibit genetic hypertension similar to that of Dahl salt-sensitive rats (37). In congestive heart failure, PKCα, β, γ, and ε decreased and PKCζ was not significantly modified when rabbits underwent heart failure induced by a double hemodynamic overload (aortic insufficiency followed by an aortic stenosis) (38). PKCα and β increased and PKCε was not significantly changed in the failing human heart due to dilated and ischemic cardiomyopathy (15).…”
Section: Discussionmentioning
confidence: 99%
“…PKC activities were determined by slight modifications of previously described procedures (13)(14)(15)(16). Briefly, the cytosolic and the particulate fractions (above) were partially purified by passage through DE-52 cellulose columns (15,16) and assayed either for Ca 2ϩ -stimulated PKC activity using histone H 1 as substrate (histone kinase) or for Ca 2ϩ -independent PKC activity using the synthetic substrate of PKC ⑀ , Epep (Epep kinase).…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, the cytosolic and the particulate fractions (above) were partially purified by passage through DE-52 cellulose columns (15,16) and assayed either for Ca 2ϩ -stimulated PKC activity using histone H 1 as substrate (histone kinase) or for Ca 2ϩ -independent PKC activity using the synthetic substrate of PKC ⑀ , Epep (Epep kinase). The reaction mixtures contained 20 mM Tris-HCl (pH 7.5), 10 M [␥-32 P]ATP, 10 mM magnesium acetate, 0.75 mM CaCl 2 , 50 g/ml leupeptin, either 100 g/ml histone or 50 g/ml Epep, with or without 30 M phosphatidylserine, and 0.5 M dioleyl-sn-glycerol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, PKCε expression in the cytosol and membrane was not significantly different between failing and non-failing hearts (Bowling et al 1999). PKCα, β, ε, ζ, and γ were found to be expressed in healthy rabbit hearts, but when heart failure was induced, western blotting showed a decreased PKC activity and expression of the PKC isoforms α, β 1 , γ, and ε (Rouet- Benzineb et al 1996). Belin et al (2007) studied PKCα quantity, activity, and signaling to myofilaments in rat with early and end-stage congestive heart failure and found that PKCα expression and activation was unaltered in early heart failure, but it did increase in endstage heart failure.…”
Section: Activation and Distribution Of Pkc Isoformsmentioning
confidence: 99%